Community-Based Flood Monitoring and Mitigation Education through the Implementation of Biopore Systems in Cangkuang Kulon Village - Rd. Rohmat Saedudin; Cindy Muhdiantini; Mega Fitri Yani (NJCOM: Community Service Journal, 2026)
Floods are among the most common hydrometeorological disasters in Indonesia and have significant impacts on the social and economic well-being of communities. Cangkuang Kulon Village, Bandung Regency, is one of the areas vulnerable to flooding, highlighting the need to strengthen community capacity in disaster mitigation. This community service program aimed to enhance public understanding of community-based flood monitoring and mitigation through the implementation of biopore systems and the provision of supporting facilities. The activity involved village officials and local community members. The implementation methods included educational sessions, interactive discussions, and the handover of biopore construction equipment. The results indicated an improvement in community understanding of environmental monitoring, the application of biopore systems as a flood mitigation measure, and the importance of community participation in building sustainable disaster preparedness.